Monocytes from Patients with Indeterminate and Cardiac Forms of Chagas' Disease Display Distinct Phenotypic and Functional Characteristics Associated with Morbidity - Souza, Paulo E. A. (American Society for Microbiology, 2004)
Many studies have demonstrated that monocyte-derived macrophages display critical activities in immunity to parasites. The ability of these cells to process and present antigens, produce cytokines, and provide costimulatory signals demonstrates their pivotal role in initiating immune responses. Although potential modulatory function has been attributed to monocytes from patients with Chagas' disease, a systematic phenotypic and functional analysis of these cells has not been performed. In this work, we analyzed the ex vivo expression of important surface molecules (CD11b and HLA-DR) and immunoregulatory cytokines (interleukin-10 [IL-10], IL-12 and tumor necrosis factor alpha [TNF-α]) in CD14(+) and CD14(−) monocytes from Chagas' disease patients with polar clinical forms of the disease: indeterminate or severe cardiac. We also evaluated the influence of in vitro infection with T. cruzi in the expression of such molecules. We observed that monocytes from indeterminate-disease patients display lower levels of HLA-DR than those from noninfected individuals both ex vivo and after in vitro infection with T. cruzi. Although ex vivo expression of CD11b was similar among the groups, in vitro infection led to decreased expression of this molecule by monocytes from Chagas' disease patients but not from noninfected individuals. Analysis of the expression of immunoregulatory cytokines showed that while monocytes from indeterminate-disease patients are committed to IL-10 expression, a higher percentage of monocytes from cardiac-disease patients express TNF-α after exposure to live parasites. These results suggest that monocytes from indeterminate-disease patients display modulatory characteristics related to low HLA-DR and high IL-10 expression whereas monocytes from cardiac-disease, patients may be committed to induction of inflammatory responses related to high TNF-α expression.